Implementasi Program Desa Mandiri Pangan di Kecamatan Pulubala Kabupaten Gorontalo - Djibran, Moh. Muchlis (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The Food Independent Village Program (Demapan) aims to increase the empowerment of poor rural communities by managing and utilizing their resources optimally. These efforts are made to achieve food independence for households and communities, especially for villages with high poverty levels. Food independent villages through empowering the community to play an active role by realizing the availability, distribution and consumption of food from time to time as well as utilizing socio-economic institutions. This research was conducted in five villages in Pulubala District, Gorontalo Regency. The aim of this research is to determine the implementation of the Food Independent Village Program in Pulubala District. The population based on the survey in this study was 50 farmers. This research method is qualitative descriptive. The research results show that the implementation of the Food Independent Village Program in Pulubala District, Gorontalo Regency has gone according to expectations.